There are more football injury prevention reviews than randomised controlled trials. Time for more RCT action! - Bricca, A.; Juhl, C. B.; Bizzini, M.; Andersen, T. E.; Thorborg, K. (British Journal of Sports Medicine, 2018)
Football is the most popular sport worldwide, and participation in football at any level is associated with numerous health benefits.1 However, participation in football at any level incurs a risk of sustaining musculoskeletal injuries.2 3 Effective injury prevention strategies are needed. The first formal injury prevention randomised controlled trial (RCT) in football was published in 1983.4 We performed a scoping systematic review to provide an overview of the published articles on injury prevention in football.